2013
DOI: 10.4172/2157-7064.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pesticide Residues in Vegetables by Different Chromatographic Techniques

Abstract: Cypermethrin, chlorpyrifos and imidacloprid residues were determined in different vegetables. During 2013, samples were collected from different six major vegetable markets from Lahore. Ethyl acetate was used for extraction, whattman fluted filter and charcoal was used for cleaning procedure. High performance thin layer chromatography was used for detection, as well as quantification of pesticides. Confirmation of results was done by using gas chromatography/mass spectrophotometer. From results, it was conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…The findings of this study are comparable to the findings of the study conducted by Munawar and Hameed [14] on cabbage samples collected from markets in Pakistan that revealed the concentrations of chlorpyrifos ranging from ND to 0.075 mg/kg and those of cypermethrin ranging from ND to 0.14 mg/kg. The field study on cabbage samples conducted in Tanzania by Meela [10] did not detect the chlorpyrifos and cypermethrin; instead it reported fenitrothion at concentrations up to 2.56 mg/kg.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study are comparable to the findings of the study conducted by Munawar and Hameed [14] on cabbage samples collected from markets in Pakistan that revealed the concentrations of chlorpyrifos ranging from ND to 0.075 mg/kg and those of cypermethrin ranging from ND to 0.14 mg/kg. The field study on cabbage samples conducted in Tanzania by Meela [10] did not detect the chlorpyrifos and cypermethrin; instead it reported fenitrothion at concentrations up to 2.56 mg/kg.…”
Section: Resultssupporting
confidence: 89%
“…The results obtained from this study show that the concentrations of chlorpyrifos were far above the concentrations obtained by Munawar and Hameed [14] who found that spinach samples collected from six markets in Pakistan contained chlorpyrifos at levels ranging from ND to 0.184 mg/kg while the concentrations of cypermethrin ranging from 0.01 to 0.156 mg/kg were comparable to the concentrations of cypermethrin obtained in this study. The field study on Amaranths spp.…”
Section: Resultssupporting
confidence: 69%
“…As the groundwater, sewage water is used for irrigation the pesticides are bioaccumulated in the vegetables and fruits. Pesticides Cypermethrin, Chlorpyrifos, and imidacloprid were detected in the 65-70% of the Pumpkin, okra, eggplant; cucumber spinach and cabbage vegetables collected from Lahore city market (Munawar & Hameed, 2013). About 38% of fruit samples and 16% of vegetables grown in Poland were contaminated with more than one pesticide beyond the permissible limit was the findings of Szpyrka et al, (2015).…”
Section: Pesticides In Vegetables and Fruitsmentioning
confidence: 97%
“…Samples were extracted with ethyl acetate, extracts were cleaned up on a charcoal column, methanol-ammonia mobile phase was used with silica gel plates, and potassium iodide and o-tolidine were applied to detect yellowish-brown zones of the pesticides. [57] A TLC method for simultaneous QC determination of the herbicides 2,4-D, 2,4,5-T, MCPA, 2,4-DP, MCPP, dicamba, and MCPB in natural surface and ground water samples was developed and validated. Silica gel 60 F 254 plates were developed with benzene-dioxane-acetic acid (45:10:2), and scanning was at 280 nm.…”
Section: Tlc-msmentioning
confidence: 99%